Exploring the Genomic Patterns in Human and Mouse Cerebellums Via Single-Cell Sequencing and Machine Learning Method - Li, ZhanDong; Wang, Deling; Liao, HuiPing; Zhang, ShiQi; Guo, Wei; Chen, Lei; Lu, Lin; Huang, Tao; Cai, Yu-Dong (Frontiers in Genetics, 2022)
In mammals, the cerebellum plays an important role in movement control. Cellular research reveals that the cerebellum involves a variety of sub-cell types, including Golgi, granule, interneuron, and unipolar brush cells. The functional characteristics of cerebellar cells exhibit considerable differences among diverse mammalian species, reflecting a potential development and evolution of nervous system. In this study, we aimed to recognize the transcriptional differences between human and mouse cerebellum in four cerebellar sub-cell types by using single-cell sequencing data and machine learning methods. A total of 321 387 single-cell sequencing data were used. The 321 387 cells included four cell types, i.e., Golgi (5048, 1.57%), granule (250 307, 77.88%), interneuron (60 526, 18.83%), and unipolar brush (5506, 1.72%) cells. Our results showed that by using gene expression profiles as features, the optimal classification model could achieve very high even perfect performance for Golgi, granule, interneuron, and unipolar brush cells, respectively, suggesting a remarkable difference between the genomic profiles of human and mouse. Furthermore, a group of related genes and rules contributing to the classification was identified, which might provide helpful information for deepening the understanding of cerebellar cell heterogeneity and evolution.